Impact of lockdown in COVID 19 on glycemic control in patients with type 1 Diabetes Mellitus (2020)
Background and aims: COVID 19 is a novel pandemic affecting globally. Although no reliable data suggests that patients of well controlled Type 1 Diabetes Mellitus (T1DM) being at increased risk of becoming severely ill with SARS-CoV2, but lockdown may impact patients with T1DM requiring regular medications and follow up. Hence this study was planned to see the impact of lockdown on glycemic control in patients with T1DM. Methods: A cross sectional study was done in T1DM patients in whom a structured questionnaire was administered on follow up within 15 days after lockdown. Data regarding hypoglycemic and hyperglycemic episodes, Diabetic ketoacidosis (DKA), insulin dose missed, regular glucose monitoring, dietary compliance, physical activity, hospitalization during the phase of lockdown was taken. Average blood glucose and HbA1C of lockdown phase was compared with the readings of prelockdown phase. Results: Out of 52 patients, 36.5% had hyperglycemic and 15.3% had hypoglycemic episodes. Insulin dose was missed in 26.9%, glucose monitoring not done routinely in 36.5% and 17.4% were not diet compliant during lockdown. Average blood glucose during lockdown phase was 276.9 ± 64.7 mg/dl as compared to 212.3 ± 57.9 mg/dl during prelockdown phase. Mean HbA1c value of lockdown (10 ± 1.5%) which was much higher that of pre lockdown (8.8 ± 1.3%) and the difference was statistically significant (p < 0.05). Conclusion: Glycemic control of T1DM patients has worsened mainly due to non availability of insulin/ glucostrips during lockdown period. There is a need for preparedness in future so that complications can be minimised.